GENETIC MUTATIONS AND THEIR CONNECTION WITH HEREDITARY DISEASES (International journal of artificial intelligence, 2025)
This article analyzes the types of genetic mutations, their causes, and the hereditary diseases that develop as a result of such mutations. The effects of mutations on key biological processes in the human body, the anatomical changes they cause, and the mechanisms by which they are passed from one generation to the next are scientifically explored.